An adenoviral-vectored vaccine confers seroprotection against capsular group B meningococcal disease - Dold, C; Marsay, L; Wang, N; Silva-Reyes, L; Clutterbuck, E; Paterson, GK; Sharkey, K; Wyllie, D; Beernink, PT; Hill, AV; Pollard, AJ; Rollier, CS (American Association for the Advancement of Science, 2023)
Adenoviral-vectored vaccines are licensed for prevention of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and Ebola virus, but, for bacterial proteins, expression in a eukaryotic cell may affect the antigen's localization and conformation or lead to unwanted glycosylation. Here, we investigated the potential use of an adenoviral-vectored vaccine platform for capsular group B meningococcus (MenB). Vector-based candidate vaccines expressing MenB antigen factor H binding protein (fHbp) were generated, and immunogenicity was assessed in mouse models, including the functional antibody response by serum bactericidal assay (SBA) using human complement. All adenovirus-based vaccine candidates induced high antigen-specific antibody and T cell responses. A single dose induced functional serum bactericidal responses with titers superior or equal to those induced by two doses of protein-based comparators, as well as longer persistence and a similar breadth. The fHbp transgene was further optimized for human use by incorporating a mutation abrogating binding to the human complement inhibitor factor H. The resulting vaccine candidate induced high and persistent SBA responses in transgenic mice expressing human factor H. The optimized transgene was inserted into the clinically relevant ChAdOx1 backbone, and this vaccine has now progressed to clinical development. The results of this preclinical vaccine development study underline the potential of vaccines based on genetic material to induce functional antibody responses against bacterial outer membrane proteins.